Welfare Standards and Merger Analysis: Why not the Best? - Kenneth Heyer (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2006)
Over the past several decades, there has emerged a rough consensus among professional antitrust practitioners, and within the law and economics community generally, that the "competition" referred to in our antitrust statutes is not to be interpreted simply as pre-merger rivalry among entities. Rather, it is best viewed as a process, the outcome of which is welfare, with welfare-not "rivalry"–being the object of interest. Consistent with this interpretation, scholars, competition authorities, and the courts have come to treat antitrust law as condemning only those mergers whose effect may be substantially to reduce welfare. That having been said, there remains a question of which welfare standard to use, and exactly whose welfare to consider. Several candidates suggest themselves. I argue in this paper for using the so-called "Total Welfare" standard, rather than the more commonly employed "Consumer Welfare" standard. In doing so, I respond to three broad objections that have been raised. One is that use of a total welfare standard conflicts with antitrust law, or at least with legal precedent. A second is that employing a total welfare standard would be more costly for antitrust agencies than employing one or another flavor of a consumer welfare standard. A third is that the total welfare standard ignores important distributional considerations-considerations that are better treated under some form of consumer welfare standard. Each of these objections is evaluated, and ultimately found unpersuasive.
Keywords: 330